2015
DOI: 10.1038/ncomms7302
|View full text |Cite
|
Sign up to set email alerts
|

Genomic landscape of paediatric adrenocortical tumours

Abstract: Pediatric adrenocortical carcinoma is a rare malignancy with poor prognosis. Here we analyze 37 adrenocortical tumors (ACTs) by whole genome, whole exome and/or transcriptome sequencing. Most cases (91%) show loss of heterozygosity (LOH) of chromosome 11p, with uniform selection against the maternal chromosome. IGF2 on chromosome 11p is overexpressed in 100% of the tumors. TP53 mutations and chromosome 17 LOH with selection against wild-type TP53 are observed in 28 ACTs (76%). Chromosomes 11p and 17 undergo co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
175
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 168 publications
(187 citation statements)
references
References 49 publications
3
175
0
9
Order By: Relevance
“…External data were downloaded from the European Genome-Phenome Archive (EGA; https://www.ebi.ac.uk/ega/home) using the accession numbers EGAD00001000085, EGAD00001000135, EGAD00001000159, EGAD00001000160, EGAD00001000161, EGAD00001000162, EGAD00001000163, EGAD00001000164, EGAD00001000165, EGAD00001000259, EGAD00001000260, EGAD00001000261, EGAD00001000268, and EGAD00001000269 [49][50][51][52][53][54][55][56][57][58][59][60][61][62] ; internal datasets are related to previous PMIDs 27748748, 27479119, 26923874, 25670083, 25253770, 24972766, 24553142, 25135868, 26632267, 26179511, 24651015, 28726821, 23817572, 25962120, 26294725 17,19,44,63-74 (Supplementary Note 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…External data were downloaded from the European Genome-Phenome Archive (EGA; https://www.ebi.ac.uk/ega/home) using the accession numbers EGAD00001000085, EGAD00001000135, EGAD00001000159, EGAD00001000160, EGAD00001000161, EGAD00001000162, EGAD00001000163, EGAD00001000164, EGAD00001000165, EGAD00001000259, EGAD00001000260, EGAD00001000261, EGAD00001000268, and EGAD00001000269 [49][50][51][52][53][54][55][56][57][58][59][60][61][62] ; internal datasets are related to previous PMIDs 27748748, 27479119, 26923874, 25670083, 25253770, 24972766, 24553142, 25135868, 26632267, 26179511, 24651015, 28726821, 23817572, 25962120, 26294725 17,19,44,63-74 (Supplementary Note 1).…”
Section: Methodsmentioning
confidence: 99%
“…Ninety-five per cent of the patients were under 18 years of age (or age unspecified but confirmed age group paediatric), but available data were included for patients up to 25 years, as these were considered relevant for cancer types that typically peak at a young age. All centres have approved data access and informed consent had been obtained from all patients.External data were downloaded from the European Genome-Phenome Archive (EGA; https://www.ebi.ac.uk/ega/home) using the accession numbers EGAD00001000085, EGAD00001000135, EGAD00001000159, EGAD00001000160, EGAD00001000161, EGAD00001000162, EGAD00001000163, EGAD00001000164, EGAD00001000165, EGAD00001000259, EGAD00001000260, EGAD00001000261, EGAD00001000268, and EGAD00001000269 [49][50][51][52][53][54][55][56][57][58][59][60][61][62] ; internal datasets are related to previous PMIDs 27748748, 27479119, 26923874, 25670083, 25253770, 24972766, 24553142, 25135868, 26632267, 26179511, 24651015, 28726821, 23817572, 25962120, 26294725 17,19,44,63-74 (Supplementary Note 1).The final cohort included 914 individual patients of no more than 25 years of age including primary tumours for 879 patients with 47 matched relapsed tumours, and an additional 35 independent relapsed tumours ( Supplementary Tables 1, 2). Deep-sequencing (~ 30× ) whole-genome data (WGS) were available for 547 samples with matched control, whole-exome sequencing (WES) for 414, and low-coverage whole-genome sequencing (lcWGS) for an additional 54 germline and 186 tumour samples.…”
mentioning
confidence: 99%
“…Subsequent studies have reported frequent ATRX loss (but not DAXX loss) in astrocytoma, leiomyosarcoma, dedifferentiated liposarcoma and other tumor types, and the loss of ATRX has been highly correlated with the alternative lengthening of telomeres phenotype. 6,12,13,[17][18][19][20][21] However, knockdown of ATRX or DAXX has not led to alternative lengthening of telomeres, and patients with germline ATRX mutations do not appear to be cancer prone. 18,22 In addition, although loss of either ATRX or DAXX is perfectly associated with alternative lengthening of telomeres in pancreatic neuroendocrine tumors, the situation is more complex in sarcomas.…”
mentioning
confidence: 99%
“…Among HLA class II antigens, HLA-DPA1 expression was most significantly associated with DFS after adjustment for tumor weight and stage (Pinto et al 2016). Integrative analysis of genomic alterations of pediatric ACT identified a highrisk group characterized by concomitant TP53 and ATRX mutations, massive structural variations and frequent background mutations and higher expression of genes associated with chromosome instability and cell cycle (Pinto et al 2015). A recent study in pediatric ACT showed that an elevated KI67 LI and MKI67 overexpression are associated with reduced DFS.…”
Section: Markers Of Malignancy Are Different In Pediatric Act Comparementioning
confidence: 99%